Implementasi Program Percepatan Sertifikasi Barang Milik Daerah Berupa Tanah pada BPPKAD Kabupaten Gresik: Implementation of the Acceleration Program for Certification of Regional Property in the Form of Land at BPPKAD Gresik Regency - Adinda Rahmania Putri; Siti Musyarofah (Edujavare Publishing, 2024)
This accelerated certification program is a solution for the government in protecting assets in the form of land which is very vulnerable to problems. The aim of this research is to analyze and evaluate the implementation of the regional property certification program. This research uses a qualitative approach with the action research method, where this method has five stages, namely: Diagnosing, Action Planning, Taking Action, Evaluating, Specifying Learning. Data collection techniques were carried out by means of direct observation and interviews with regional property managers in the area of BPPKAD district asset management. Gresik. The results of the research show that with the implementation of this accelerated asset certification program, it can be recognized that the implementation has gone well, even the regional land assets that have been certified have exceeded the specified targets. However, BPPKAD Kab. Gresik also still needs to carry out outreach regarding asset security and regular monitoring activities. Due to several obstacles, this program did not run optimally.